Genomic attributes differ between Vibrio parahaemolyticus environmental and clinical isolates including pathotypes. Issue 3 (30th August 2021) - Meparambu Prabhakaran, Divya; Patel, Hardip R.; Sivakumar Krishnankutty Chandrika, Sivakumar; Thomas, Sabu
Summary: Vibrio parahaemolyticus is a marine bacterium and causes opportunistic gastroenteritis in humans. Clinical strains of V. parahaemolyticus contain haemolysin and type III secretion systems (T3SS) that define their pathotype. A growing number of strains isolated recently from the environment have acquired these virulence genes constituting a pool of potential pathogens. This study used comparative genomics to identify genetic factors that delineate environmental and clinical V. parahaemolyticus population and understand the similarities and differences between the T3SS2 phylotypes. The comparative analysis revealed the presence of a cluster of genes belonging to bacterial cellulose synthesis ( bcs ) in isolates of environmental origin. This cluster, previously unreported in V. parahaemolyticus, exhibit significant similarity to that of Aliivibrio fischeri, and might dictate a potentially new mechanism of its environmental adaptation and persistence. The study also identified many genes predicted in silico to be T3SS effectors that are unique to T3SS2β of tdh − trh + and tdh + trh + pathotype and having no identifiable homologue in tdh + trh − T3SS2α. Overall, these findings highlight the importance of understanding the genes and strategies V. parahaemolyticus utilize for the myriad interactions with its hosts, either marine invertebrates or humans.